Optimization for Degradation of Commercial Reactive Yellow Dye 145 Through Fenton’s Reagent - Mahmood, Ayesha; Ali, Shaukat; Saleem, Hamna; Hussain, Tanveer (Asian Journal of Chemistry, 2011)
Among advanced oxidation processes, oxidation using Fenton's reagent is an attractive treatment for the effective decolourization and degradation of dye because of its low cost and the lack of toxicity of the reagents (i.e., Fe2+ and H2O2 and solar radiation). The degradation of reactive yellow 145 dye by Fenton and photo-Fenton processes was investigated. The degradation rate was strongly dependent on pH, initial concentrations of Fe2+, H2O2, temperature and light intensity. The effects of these parameters have been studied and optimum operational conditions of these two processes were found. The optimum conditions were found at pH 3 for these processes. The decolourization experiments indicate that dye can be effectively decolourized using Fenton and photo-Fenton processes with a little difference between the two processes, 91.4 and 97.8 % within 0.5 h, respectively for optimal conditions. The difference in docolourization is not similar to COD removal: with Fenton process there is significant increment (52.27 % COD removal) relatively to photo-Fenton process (only 38.63 % COD removal).